Formulation of Correctional System Model in Corruption Enforcement in Indonesia - Mahardika, Dinar; Terima, Tian; Kurnia, Kamal Fahmi; Pratama, Aditya Erwin; Zainudin, Arif (International Journal of Criminology and Sociology, 2021)
Corruption in Indonesia requires the right formulation. The rule of law and punishment system in Indonesia is still weak against criminals. This paper tries to find the right formula in punishing corruptors because the existing punishment system is still breakable and is deemed ineffective in preventing it. This paper belongs to a type of normative approach with a descriptive-analytical. This paper reveals that there are weaknesses in the rule of law in corruption compromise, resulting in increasing corruption every year. Data from ICW in 2018 shows that corruption is still considered a common crime, and the current punishment system does not reflect the firmness in determining the maximum punishment. It is exacerbated by the sale and purchase of facilities in prisons, which results in public distrust of the law. In other countries, Indonesia must be more severe in punishing bribery and corruption, including extraordinary crimes against the people. The conclusion in this paper is to formulate a religious and moral approach in punishing corruptors such as social sanctions, public humiliation, being a cleaning worker, life imprisonment, being exiled, taking political rights, even being humiliated in public so that it becomes a new formula in corrupt penalty system.